ABORDAREA MACRO ȘI MICRO SOCIALĂ A CALITĂȚII VIEȚII - Sterpu, Vladimir (CEP USM, 2024)
The content of the article reflects the synthesis of scientific approaches to the quality of life at macro and microsocial levels. The purpose of the study lies in the synthesis of theoretical- empirical approaches regarding the quality of life assessment. Achieving the purpose of the research was possible by solving the following objectives, such as: studying the evolution of theoretical- empirical approaches regarding the quality of life; generalization of theoretical-empirical approaches of life quality at macro and microsocial levels; identification of methodological tendencies in the macro and social approach of life quality. Based on the bibliographic referential, conclusions were formulated with reference to the study subject.
MACRO AND MICRO SOCIAL APPROACH OF THE QUALITY OF LIFE
STERPU, Vladimir. Abordarea macro și micro socială a calității vieții. În: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Științe umanistice și sociale, 9-10 noiembrie 2023. CEP USM, 2024, pp. 405-412. ISBN 978-9975-62-691-0 (PDF).
Keywords: life quality; macro level; micro level